Attributes of ethical leadership in leading good governance - Othman, Zaleha; Abdul Rahman, Rashidah (Universiti Malaysia Sarawak, 2014)
The aim of this study is to present a practical and rational perspective of corporate governance. Specifically, this study explores the concept of ethical leadership in relation to corporate governance.It introduces morality as a core element in creating good governance practices, starting from the premise that corporate governance is subjective.We must therefore consider the social reality in which corporate governance is based.As such, inquiry about the social reality is required. Based on that premise, qualitative methodology is employed to gather views about the concept of ethical leadership in the context of corporate governance.The socially constructed reality of this study is represented by individuals who were categorized as experts and corporations known to have a high standard of corporate governance.Views from the subjects about ethics in the perspective of corporate governance were gathered.Content analysis was used to analyse the data.Triangulation techniques of data collection were adopted to provide richness and thickness to the data. Interviews, document analysis and observations were used to understand the reality of the research issue.Triangulation techniques support the validation and reliability of data.The research found several ethical leadership attributes that are essential to guide corporate governance practices.They are fundamental elements that have emerged from the data.This paper develops a framework around the dimensions of ethical leadership relative to the Malaysian business environment. The paper advances an understanding of ethical leadership in the Malaysian business environment and offers an agenda for future research in the corporate governance field.